Testing detection and discrimination of vegetation chemical cues in the subterranean rodent Ctenomys talarum - Schleich, Cristian (2010)
Previous studies on the subterranean rodent Ctenomys talarum (tuco-tuco) have shown that this species has the ability to use olfaction to orient their digging while foraging. As a continuation of these works, we assess whether direct contact with vegetation chemical signals is required for food odour recognition, and whether this subterranean rodent is also able to discriminate plants of different nutritional quality by the chemical signals released by them into the soil. First, we test animal responses to plant extracts and controls (water) covered with a wire mesh or without it. Also, we assess individual digging response in an artificial Y-maze whose arms were filled with soil in which plants of different nutritional quality have been grown. The results of this study suggest that (i) volatile chemical cues allow food odour recognition and direct contact with the odour source does not enhance such recognition in C. talarum, and (ii) olfaction could play a key role in the finding of food patches, allowing individuals to direct their excavation towards plant species of high nutritional quality. © 2010 Dipartimento di Biologia Evoluzionistica dell'Universitá, Firenze, Italia.